2010
DOI: 10.5664/jcsm.27763
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Apnea-Hypopnea Index Determined by the S8 Auto-CPAP, a Continuous Positive Airway Pressure Device, in Patients with Obstructive Sleep Apnea-Hypopnea Syndrome

Abstract: Objective: Continuous positive airway pressure (CPAP) has been established as an effective treatment for obstructive sleep apnea-hypopnea syndrome (OSAHS). Recently, several auto-CPAP devices that can detect upper airway obstructive events and provide information about residual events while patients are on CPAP have come into clinical use. The purpose of this study was to compare the apnea-hypopnea index (AHI) determined by the S8 auto-CPAP device with the AHI derived by polysomnography in patients with OSAHS.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 14 publications
1
27
0
2
Order By: Relevance
“…The latter is especially the case if detected events are apneas. As previously reported 27,28,30,31 we found that the correlation between devicedetected and manually scored breathing events was higher for apneas than for hypopneas. This is not surprising because the polysomnographic definition of hypopnea includes oxygen desaturations and arousals that are not detected by the APAP device.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The latter is especially the case if detected events are apneas. As previously reported 27,28,30,31 we found that the correlation between devicedetected and manually scored breathing events was higher for apneas than for hypopneas. This is not surprising because the polysomnographic definition of hypopnea includes oxygen desaturations and arousals that are not detected by the APAP device.…”
Section: Discussionsupporting
confidence: 84%
“…11,[25][26][27][28][29][30][31] A review of the more recent studies concluded that the assessment of the residual apnea index was more robust than the hypopnea index, and that the event detection algorithms tended to underestimate the AHI at higher manually scored AHI values (AHI > 10 events/h) and overestimate the AHI at lower manually scored AHI values (AHI < 10 events/h). [25][26][27][28]30,31 From a clinical perspective, the authors concluded that these event detection algorithms can be used if the data are at either end of the spectrum. Treatment of OSA is likely to be effective if AHI < 10 events/h, and is likely to be inadequate if AHI > 20 events/h.…”
Section: Discussionmentioning
confidence: 99%
“…The AHI estimated by Auto-titrating CPAP has been shown to correlate with AHI from polysomnography. 25,26 At this consultation patients were asked whether they wished to continue CPAP long-term. Occasionally patients were offered an extension of the two-week period or a second trial either because they had developed a problem which compromised their ability to use CPAP (for instance upper respiratory tract infection) or if they had severe symptomatic disease, had struggled with CPAP initially and were willing to have another try.…”
Section: Methodsmentioning
confidence: 99%
“…En la práctica general, CPAP se utiliza con más frecuencia para el tratamiento de patología respiratoria del sueño. Algunos de estos dispositivos de CPAP están diseñados para detectar diversos grados de obstrucción de las vías respiratorias superiores y luego ajustar el nivel de presión para mantener abierta la vía aérea (Auto CPAP) (Figura 3) 11 . Algunos pacientes que no toleran CPAP manifiestan dificultad al exhalar contra la presión de la vía aérea generada por el dispositivo, especialmente en pacientes cuya presión terapéutica necesaria es alta (p.…”
Section: Modos Ventilatoriosunclassified